Association of Age With Polypharmacy and Risk of Drug Interactions With Antiretroviral Medications in HIV-Positive Patients. (November 2013) - Tseng, Alice; Szadkowski, Leah; Walmsley, Sharon; Salit, Irving; Raboud, Janet
Background: Interactions between antiretroviral (ARV) therapy and medications to treat age-related comorbidities are a growing concern in the aging HIV population.Objective: To investigate the association of age with potential drug-drug interactions (PDDIs) involving ARVs.Methods: We studied ARV-treated patients attending a tertiary care center. PDDIs were classified as "red flag" (contraindicated) or "orange flag" (use with caution or dose adjustment). Logistic regression was used to determine the association of age with the occurrence of ≥1 PDDI.Results: Of 914 patients (78% male, median age 49 years), older patients (age ≥50 years) were on more drugs than younger patients (total 9 vs 7; P < .0001) and were more likely to be on ritonavir-boosted protease inhibitors (PIs), integrase inhibitors, and non-ARV medications. Older patients were more likely to have ≥1 orange flag PDDI (71% vs 55%, P < .0001) and to have a red flag PDDI (5% vs 2%, P = .07), although the latter did not reach statistical significance. A 10-year increase in age was associated with an increased likelihood of ≥1 PDDI (odds ratio [OR] = 1.72; P < .0001) after adjusting for gender, race and number and class of ARVs. The effect of age was diminished after adjusting further for the number of non-ARV medications (OR = 1.28; P = .02) and use of cardiovascular drugs (OR = 1.16; P = .21).Conclusions: In our clinic population, older patients were more likely to have a PDDI because of the greater number of non-ARV medications, particularly cardiovascular agents.